Mandibular osteonecrosis following herpes zoster infection: Report of a rare case with a literature review. Issue 5 (24th May 2021) - Faure, Emilie; Engels‐Deutsch, Marc; Paraschiv, Elena‐Adinisia; Gérard, Eric; Curien, Rémi
Abstract: Any patient with a herpes zoster infection of the mandibular branch of the trigeminal nerve should benefit from early oral monitoring, especially in elderly population where traumatic dental prostheses are common, because osteonecrosis can occur. Abstract : Herpes zoster infection is a rare and little‐known etiology of osteonecrosis of the maxilla. Only a few cases have reported in the international literature. We present a rare case of right mandibular osteonecrosis following herpes zoster infection in the mandibular branch of the trigeminal nerve.